Induction of fecal cholesterol excretion is not effective for the treatment of hyperbilirubinemia in Gunn rats - Blankestijn, Maaike; van de Peppel, Ivo P; Dvorak, Ales; Capkova, Nikola; Vitek, Libor; Jonker, Johan W; Verkade, Henkjan J (Pediatric research, 2021)
BACKGROUND: Unconjugated hyperbilirubinemia, a feature of neonatal jaundice or Crigler-Najjar syndrome, can lead to neurotoxicity and even death. We previously demonstrated that unconjugated bilirubin (UCB) can be eliminated via transintestinal excretion in Gunn rats, a model of unconjugated hyperbilirubinemia, and that this is stimulated by enhancing fecal fatty acid excretion. Since transintestinal excretion also occurs for cholesterol (TICE), we hypothesized that increasing fecal cholesterol excretion and/or TICE could also enhance fecal UCB disposal and subsequently lower plasma UCB concentrations. METHODS: To determine whether increasing fecal cholesterol excretion could ameliorate unconjugated hyperbilirubinemia, we treated hyperbilirubinemic Gunn rats with ezetimibe (EZE), an intestinal cholesterol absorption inhibitor, and/or a liver X receptor (LXR) and farnesoid X receptor (FXR) agonist (T0901317 (T09) and obeticholic acid (OCA), respectively), known to stimulate TICE. RESULTS: We found that EZE treatment alone or in combination with T09 or OCA increased fecal cholesterol disposal but did not lower plasma UCB levels. CONCLUSIONS: These findings do not support a link between the regulation of transintestinal excretion of cholesterol and bilirubin. Furthermore, induction of fecal cholesterol excretion is not a potential therapy for unconjugated hyperbilirubinemia. IMPACT: Increasing fecal cholesterol excretion is not effective to treat unconjugated hyperbilirubinemia. This is the first time a potential relation between transintestinal excretion of cholesterol and unconjugated bilirubin is investigated. Transintestinal excretion of cholesterol and unconjugated bilirubin do not seem to be quantitatively linked. Unlike intestinal fatty acids, cholesterol cannot "capture" unconjugated bilirubin to increase its excretion. These results add to our understanding of ways to improve and factors regulating unconjugated bilirubin disposal in hyperbilirubinemic conditions.
Keywords: Sulfonamides; Ezetimibe; Feces; střeva; hyperbilirubinemie; Male; fluorované uhlovodíky; kyselina chenodeoxycholová; Receptors, Cytoplasmic and Nuclear; náhodné rozdělení; Criglerův-Najjarův syndrom; Bile Acids and Salts; jaterní receptor X; Cholesterol; Liver X Receptors; Bilirubin; bilirubin; mužské pohlaví; Dietary Fats; PPAR delta; žluč; Hydrocarbons, Fluorinated; haptoglobiny; Hyperbilirubinemia; žlučové kyseliny a soli; krysa rodu Rattus; dietní tuky; cholesterol; lipidy; Animals; Chenodeoxycholic Acid; potkani Gunn; Haptoglobins; zvířata; Rats; Random Allocation; Lipids; ezetimib; Rats, Gunn; Bile; Intestines; Crigler-Najjar Syndrome; receptory cytoplazmatické a nukleární; sulfonamidy; feces